Population‐genetic evidence for two species in Anopheles minimus in Thailand - CHRISTOPHER A. GREEN (2018)
ABSTRACT. Sympatric occurrence of homozygotes for two electro‐morphs controlled by a locus for octanol dehydrogenase, and the absence of heterozygotes, at two localities, indicates two isomorphic species within the taxon Anopheles minimus Theobald in Thailand. This view is supported by significant, relative deficiences of heterozygotes at other electromorphic loci. Gene frequency data are reported for seven electro‐morphic loci in An.minimus sensu lato from eleven localities: one of the newly recognized species predominated in all but one locality and the second was confined to two localities. This species pair of An.minimus s.l. was clearly distinguished from An.aconitus Donitz, An.pampanai Biittiker & Beales and An.varuna Iyengar, three species closely related to An.minimus s.l. in the series Myzomyia of Anopheles subgenus Cellia. Copyright © 1990, Wiley Blackwell. All rights reserved